The relationship of dyspnoea to function and quality of life in systemic sclerosis. Issue 5 (29th August 2007) - Baron, M; Sutton, E; Hudson, M; Thombs, B; Markland, J; Pope, J; Robinson, D; Jones, N; Docherty, P; Abu-Hakima, M; LeClercq, S; Smith, D; et al.
Abstract : Aim: Up to 50% of patients with systemic sclerosis (SSc) have complaints of dyspnoea. We evaluated the independent contributions of dyspnoea to function and health related quality of life (HRQoL) in SSc and also assessed the contributions of pulmonary hypertension, measured by the pulmonary artery systolic pressure (PASP), and interstitial lung disease, measured by the forced vital capacity (FVC), to dyspnoea. Methods: We assessed dyspnoea, PASP, FVC, function and HRQoL in a cohort of unselected patients with SSc. Multiple linear regression was used to assess the independent contributions of dyspnoea, PASP and FVC to function and HRQoL, after controlling for possible confounding variables. Results: A total of 194 patients with mean disease duration of 11.6 years were studied. Dyspnoea was a significant independent predictor of function and HRQoL. A model including age, gender, disease duration, disease severity and dyspnoea explained 33.3%, 10.6%, 39.2% and 29.4% of the variance of the Stanford Health Assessment Questionnaire, the Short-Form 36 (SF-36) mental component summary score, the SF-36 physical component summary score and the World Health Organization Disability Assessment Schedule II. PASP and FVC were significant independent predictors of dyspnoea but only 21.9% of the variance in dyspnoea was explained by age, gender, disease duration, FVC and PASP. The FVC was a significant independent predictor of function and HRQoL. Conclusion: In an unselected population of SSc patients, dyspnoea is a very important contributor to function and HRQoL. Interstitial lung disease, as measured by the FVC, contributes significantly to the sense of dyspnoea, function and HRQoL in SSc. Pulmonary hypertension, assessed echocardiographically by the PASP, predicts the degree of dyspnoea but not function and HRQoL in SSc.